Review of the family Veigaiidae (Acari: Mesostigmata) in Iran with a key to the species - Hajizadeh, Jalil (Journal of Biological Studies, 2023)
Four species of veigaiid mites were collected from Guilan province in Northern Iran. This paper provides a checklist for veigaiid mites species recorded from Iran, with a key for identification of the species.